Sustainability Agreements and Green Collaboration: Challenges and Opportunities within the Indonesian Competition Law Framework - Diana Fitriana; Mella Ismelina Farma Rahayu; Sugeng Sugeng; Andre Jr Cardenas (Fiat Justisia: Jurnal Ilmu Hukum, 2026)
This article examined the emerging concept of sustainability collaboration within Indonesia's competition law framework, highlighting the need to reconcile environmental sustainability with effective market competition. Indonesian competition law, particularly Law No. 5 of 1999, traditionally prohibited horizontal agreements under a rigid approach, whereas global developments increasingly recognized sustainability agreements that generated long-term consumer welfare. This study employed normative legal research with a comparative approach, using the regulatory frameworks of the European Union and the United Kingdom as benchmarks. The analysis identified a significant regulatory gap in Indonesia, where Article 50 of Law No. 5 of 1999 did not accommodate environmental efficiencies such as carbon reduction and sustainable supply chains. To address this gap, the study proposed revitalizing the public interest exception, adopting a dedicated KPPU Regulation on Sustainability Agreements, and introducing an open door policy to provide greater legal certainty for businesses. It concluded that shifting toward a long-term consumer welfare standard was essential to support both competitive markets and sustainable economic development in Indonesia.